An overview of plant-autochthonous microorganisms and fermented vegetable foods - Torres, Sebastián (2020)
Fermented plant-based foods and beverages constitute foods of high nutritional and functional value with appreciated health beneficial effects. They represent a natural and sustainable alternative to counteract the large wastage of vegetables and fruits due to their short shelf life. Usually, the use of controlled fermentation process using autochthonous microorganisms adapted to their vegetable matrix is preferred instead of traditionally spontaneous fermentation to designing fermented vegetable foods with the desirable sensory, technological, nutritional and functional properties. This review summarizes the autochthonous microorganisms selected as starters for the successful fermentation of vegetables and fruits. The main beneficial properties of autochthonous starters and fermented vegetable products with a focus on human health are revised.